INTER-CULTURAL NON-VERBAL COMMUNICATION STRATEGIES IN INDONESIAN AND THAILAND STUDENTS’ INTERACTION - Baso Muammar; Serliah Nur (UIN Alauddin Makassar, 2015)
Abstract This research is about inter-cultural non-verbal communication strategies in Indonesian and Thailand students’ interaction which is included in the Kinesics of Novinger’s theory. The objectives of research are finding out the description of the kinds of non-verbal communication strategies used among students and the ways of non-verbal communication to the students. This research applies descriptive quantitative method. The research instruments are documentation and questionnaire. The data analysis showed that there were 39 kinds of non-verbal communication. There were 16 kinds of Gestures, 6 kinds of Eye Contact, 7 kinds of Facial Expressions, 6 kinds of Touch, and 4 kinds of Posture. The result of descriptive analysis showed the rate percentage of non-verbal communication strategies that have big roles in communication between Indonesian and Thailand students were 90% gesture and 10% eye contact. Finally, non-verbal communication mostly functions as substituting verbal messages, elaborating verbal messages, transmitting telling, etc.Abstract This research is about inter-cultural non-verbal communication strategies in Indonesian and Thailand students’ interaction which is included in the Kinesics of Novinger’s theory. The objectives of research are finding out the description of the kinds of non-verbal communication strategies used among students and the ways of non-verbal communication to the students. This research applies descriptive quantitative method. The research instruments are documentation and questionnaire. The data analysis showed that there were 39 kinds of non-verbal communication. There were 16 kinds of Gestures, 6 kinds of Eye Contact, 7 kinds of Facial Expressions, 6 kinds of Touch, and 4 kinds of Posture. The result of descriptive analysis showed the rate percentage of non-verbal communication strategies that have big roles in communication between Indonesian and Thailand students were 90% gesture and 10% eye contact. Finally, non-verbal communication mostly functions as substituting verbal messages, elaborating verbal messages, transmitting telling, etc.